Consumo de energia de uma correia transportadora utilizada em unidades de armazenamento de grãos - Silva, Dayani Regina da (2020)
During the processing of agricultural products in grain storage units, conveyor belts are used to transport the grains. Due to the great potential for rationalizing the use of electrical energy in storage units, the electrical energy consumed by a conveyor belt was studied from different displacement speeds associated with different applied loads, from the installation of a frequency inverter capable of controlling the speed of travel of the conveyor belt. Voltages, currents and powers were measured for each travel speed. The frequencies of 30, 40, 50 and 60 Hz were used and the opening settings of the register coupled to the load box were used with the percentages of 10, 20, 30 and 40%. The frequency control ranges of the network, associated with the amount of grains transported by the conveyor belt, showed good results in terms of energy consumption reduction. The results obtained showed that the required power of the motor, and the electric current requested to transport the grains, had a direct influence with the frequency’s control of the network combined with the record openings. The percentage of openings in the discharge register of 30 and 40% showed better results of grain flow on the conveyor belt and energy consumption through the electric motor.